Scroll-like and platy molybdenite-3R from the Ufaley metamorphic block, South Urals: EBSD, XRD, SEM, EPMA and ICP-MS study. (13th June 2022) - Belogub, Elena V.; Shilovskikh, Vladimir V.; Rassomakhin, Michail A.; Plotinskaya, Olga Yu.; Savichev, Alexandr N.; Filippova, Ksenia A.; Kirichenko, Sergey; Spratt, John; Seltmann, Reimar
Abstract: Scroll-like crystals of molybdenite, 2–5 mm in size, were found in phengite rock from the outer contact of the granular quartz vein of the Kyshtym quartz deposit. Platy and partly scrolled molybdenite occur in the same phengite rock from the outer contact of the quartz–feldspar pegmatite of the Slyudyanogorsk mica deposit. Both occurrences are located in the Ufaley metamorphic block in the South Urals. Scroll-like molybdenite crystals can associate with platy and partly twisted crystals in the same samples. The chemical composition of molybdenite was studied by inductively coupled plasma mass spectrometry (ICP-MS) and electron probe microanalysis (EPMA). Polytypes of molybdenite were identified with electron back-scattered diffraction (EBSD) and X-ray diffraction (XRD). Both scroll-like and platy molybdenite crystals are only represented by the 3 R polytype, are enriched in Re up to 1 wt.% and contain no other significant impurities. Scroll-like molybdenite is twisted mainly around the crystallographic axis X . Twinning with a rotation of 60 degrees around the Z crystallographic axis is fixed in the plane (ab ). The most probable origin of scroll molybdenites is the consequent growth of molybdenite around nucleation centres, which are commonly represented by mica crystals. The formation of the 3 R polytype is caused by the difference in dimension of the layers enriched and depleted in rhenium.